FACEBOOK AND STUDENTS’ SUB-STANDARD ENGLISH: A CONTEXT OF BANGLADESH - Islam, Farzana Sharmin Pamela (International Journal of Language Education, 2018)
In the 21st century, one of the most frequently used social media is Facebook. This paper is going to focus on the two sides of the same issue. Firstly, the present scenario of Facebook effects on students. During teaching English in a foreign language context for almost a decade, it has been observed that the errors students make in their writing are influenced by many factors, among which the students? Facebook register and rhetoric is one of them. Secondly, this study is going to deal with the other issue that many second language/ foreign language learners have taken Facebook as a means to improve their English language skills. Lastly, the study proposes how Facebook practicing could be used as an English language teaching and learning tool, especially in Bangladesh, where English language enjoys the status of a foreign language. The paper is based on the qualitative analysis of the observations and comments of students collected through purposefully designed writing tasks assigned to students of a few selected classes of ?Basic English? and ?Composition and Communication Skills? courses of English Department in a top ranking private university located in the capital city of Bangladesh.